Pancreas transplantation: a decade of decline. Issue 4 (August 2016) - Stratta, Robert J.; Fridell, Jonathan A.; Gruessner, Angelika C.; Odorico, Jon S.; Gruessner, Rainer W.G.
Abstract : Purpose of review: In the past decade, the annual number of pancreas transplants performed in the United States has steadily declined. The purpose of this review is to discuss the multifactorial nature of this decline. Recent findings: In 2014, only 954 pancreas transplants were performed in the United States. From 2004 to 2011, the annual number of simultaneous pancreas–kidney transplants in the United States declined by 10%, whereas the corresponding annual decreases in pancreas after kidney and pancreas transplants alone were 55 and 34%, respectively. Paradoxically, this drop-off has occurred in the setting of improvements in graft and patient survival and transplanting higher risk patients. This national trend in decreasing numbers of pancreas transplants is related to a number of factors, including lack of a primary referral source, lack of acceptance by the diabetes care community, improvements in diabetes care and management, changing donor and recipient considerations, inadequate training opportunities, and increasing risk aversion because of regulatory scrutiny. Summary: Given that the incidence of end-stage renal disease secondary to diabetes remains high, a national initiative is needed to 're-invigorate' either simultaneous pancreas kidney or pancreas after kidney as preferred transplant options for appropriately selected uremic patients taking insulin irrespective of C-peptide levels or 'type' of diabetes. Moreover, many patients may benefit from pancreas transplants alone as well because all categories of pancreas transplantation are not only life-enhancing but life-extending procedures.